The usage of blood flow restriction as training intervention in physically active adults and as rehabilitation modality in knee osteoarthritis patients - Shuoqi, Li (2022)
High-intensity interval training (HIIT) can be divided into two periods: exercise and interval period. It is unclear whether there are differences in physiological and biomechanical effects when blood flow restriction (BFR) is used for an exercise intervention in different phases of HIIT. Previous BFR studies on patients with musculoskeletal injuries/problems were focused on pain and physiological outcomes. The biomechanical effects of resistance exercise with and without BFR on patients with knee osteoarthritis (OA) are unknown. Therefore, this study evaluated the long term effect of HIIT with BFR on healthy male adults and the immediate effect of BFR resistance training on patients with knee OA. Initially, 32 healthy male adults were randomised into one of the following conditions: HIIT without BFR (Control Group, n=11), HIIT with BFR during exercise phase (Experimental Group, n=10). HIIT with BFR during interval phase (Interval Group, n=11). Then, exercise intervention twice a week for 12 weeks was performed. Maximum oxygen uptake (VO2max), cycling economy, isometric knee strength, Wingate test and single leg landing biomechanical test were performed in the first, sixth and twelfth weeks. Next, 15 patients with knee OA completed two exercise sessions: elastic band resistance exercise (control group) or elastic band resistance exercise with BFR (experimental group). Heart rate, rating of perceived exertion, visual analogue scale, blood pressure and biomechanical indexes during Sit-to-Stand (STS) and gait were evaluated before and after exercise. According to the results of study, we conclude that 12 weeks of HIIT with BFR improved aerobic and anaerobic capacity in healthy male adults. Secondly, HIIT with BFR had no effects on biomechanical variables during single leg landing among healthy male adults. In addition, the application of BFR in the interval phase of HIIT improved cycling economy and fatigue index better than when applying BFR during the exercise phase. For the OA patients, the ratings of perceived exertion (RPE) was higher after elastic band exercise with BFR. Elastic-band exercise with BFR increased the internal and lateral peak pressure of the heel during gait. Notably, the elastic band exercise with BFR reduced the gait symmetry in the early stance of gait. Finally, for STS test, the OA side had a larger hip abduction angle in the sit-off phase than the healthy side, and the ground reaction force of the OA side was smaller than the healthy side in the sit-off and peak ankle flexion phases. The present study concludes that applying BFR during the interval period of HIIT can improve anaerobic capacity and cycling economy better than BFR during the exercise phase, and elastic band exercise combined with BFR is safe in patients with unilateral OA.